Legal Status of Venture Capital Fund Joint Investment Contract - Widyaputra, Michael (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 1 (2022)DO - 10.24843/JMHU.2022.v11.i01.p03, 2022)
Indonesian Venture capital companies can manage a Venture Fund (Dana Ventura) in the form of a Joint Investment Contract (Kontrak Investasi Bersama). Venture Fund is a financial instrument to collect and manage investor funds to be used for venture capital business activities. This Venture Fund is managed together with the Custodian Bank (Bank Kustodian) whose task is to store and administer the collected funds. The concept of a Venture Fund Joint Investment Contract is similar to that of a Limited Participation Mutual Funds Collective Investment Contract (Reksa Dana Berbentuk Kontrak Investasi Kolektif Penyertaan Terbatas) which also collects and manage funds together with Custodian Bank, then to invest one of which equity securities. However, Venture Fund has not been optimally exploited in Indonesia due to unclear legal status of the fund unlike the Limited Participation Mutual Funds. The issue lies on whether the fund can act in any transactions on its own. This different with Limited Participation Mutual Funds where the regulation is clear that Mutual Funds cannot act on its own. The purpose of this study is to determine the legal status of Venture Fund by comparing it with Limited Participation Mutual Funds. The research method used is a normative legal research method. The results of this study indicate that the Venture Fund is not a legal entity. Furthermore, in conducting venture capital business activities, Venture Fund should be represented by Custodian Bank, as is the case with Limited Participation Mutual Funds.